Changes of pectin substances content during the pear fruits storage with antioxidant compositions treatment - Serdyuk, Maryna; Сердюк, Марина Єгорівна; Сердюк, Марина Егоровна; Pylypenko, L.; Gaprindashvili, Nona; Гапріндашвілі, Нона Арчилівна; Гаприндашвили, Нона Арчиловна; Sukharenko, Olena; Сухаренко, Олена Іванівна; Сухаренко, Елена Ивановна; Bayberova, Svitlana; Байбєрова, Світлана Сергіївна; et al. (My University, 2019)
EN: Aim. The research is devoted to determination of the regularities of pectic substance changes in pears during refrigeration storage after antioxidant composition treatment. Methods. The content of pectic substances was determined by titerometric method, which was based on alkaline titration of the pre-selected and prepared pectic substances before and after hydrolysis. The titration results are proportional to the number of free esterified carboxylic groups, and when multiplied by the corresponding equivalents, they indicate the content of polygalacturonic acid residues in the pectic substances of the product. Results. The research showed that late ripening pears had greater content of pectic substances when put to storage. During the first 30 days of storage an insignificant (1...4%) increase of pectic substance content was observed in the fruit of control variants, during further storage (130 ... 180 days) a decrease was recorded. The loss of pectic substances by the control fruit amounted to 49 % for the entire storage period. During fruit storage after antioxidant composition treatment the increase of pectic substance content had been lasting for 2-4 months longer than of the control variants fruit, and further transfer of protopectin to the soluble pectin was taking place at a slower rate. It provided for the best preservation of pectic substances during storage. The loss of pectic substances by fruit treated with antioxidants amounted to 15 % for the entire storage period. Conclusions. Minimal losses of pectic substances (7%) were found out at the storage of pears of the varieties Victoria, Conference, Cure, Izyuminka Crimea, which had been treated with the antioxidant composition DL. UK: Дослідження присвячені визначенню закономірностей змін пектинових речовин плодів груші протягом холодильного зберігання за обробки антиоксидантними композиціями. В результаті досліджень встановлено, що в період закладання плодів на зберігання більшим вмістом пектинових речовин характеризувалися плоди груші пізнього терміну достигання. Протягом перших 30 діб зберігання у плодах контрольних варіантів спостерігалося незначне збільшення вмісту суми пектинових речовин, при подальшому зберіганні зафіксоване її зниження. При зберіганні плодів за обробки антиоксидантними композиціями зростання вмісту пектинових речовин тривало на 2 – 4 місяці довше, ніж у плодів контрольних варіантів, а подальший перехід протопектину у розчинний пектин відбувається більш повільними темпами. Це забезпечувало кращу збереженість пектинових речовин протягом зберігання. Основною тенденцією зміни показника динамічної твердості плодів було зменшення його кількісного значення протягом усього терміну зберігання незалежно від варіанту обробки. Однак, швидкості його зниження у плодів контрольних варіантів були істотно вищими. Найбільший позитивний ефект для всіх сортів плодів встановлений при використанні композиції ДЛ. RU: Исследования посвящены определению закономерностей изменений пектиновых веществ в плодах груши в течение холодильного хранения с обработкой антиоксидантными композициями. В результате исследований установлено, что в период закладки плодов на хранение большим содержанием пектиновых веществ характеризовались плоды груши позднего срока созревания. В течение первых 30 суток хранения в плодах контрольных вариантов наблюдалось незначительное увеличение содержания суммы пектиновых веществ, при дальнейшем хранении зафиксировано ее снижение. При хранении плодов с обработкой антиоксидантными композициями увеличение содержания пектиновых веществ продолжалось на 2 - 4 месяца дальше, чем у плодов контрольных вариантов, а последующий переход протопектина в растворимый пектин происходил более медленными темпами. Это обеспечивало лучшую сохранность пектиновых веществ при хранении. Основной тенденцией изменения показателя динамической твердости плодов было уменьшение его количественного значения в течение всего срока хранения независимо от варианта обработки. Однако, скорости его снижения у плодов контрольных вариантов были существенно выше. Наибольший положительный эффект для всех сортов плодов установлен при использовании композиции ДЛ.
Зміни вмісту пектинових речовин при зберіганні плодів груші за обробки антиоксидантними композиціями
Изменения содержания пектиновых веществ при хранении плодов груши с обработкой антиоксидантными композициями
Keywords: pectic substances; protopectin; pectin; antioxidants; pear fruit; refrigerated storage; пектинові речовини; протопектин; пектин; антиоксиданти; плоди груші; холодильне зберігання; пектиновые вещества; антиоксиданты; плоды груши; холодильное хранение